Mining families and gender inequalities: the construction of the feminine through popular courses on coal region Catarinense (1930-1960) (Tempo e Argumento, 2010)
At the peak of mining activity, the city of Criciúma attracted to the coal mines hundreds of people who moved from the South Coast of Santa Catarina, hoping to get work in the city. Without experience in the urban world or the mining industry, and regulated by time and productivity, thenew residents were blamed by the businessmen and local elite as responsible for the low productivity of the industry and for the medical/sanitary problems that affected the daily life of the citizens. In order to reverse the situation, the industry of coal Próspera Inc, SESI-SC and the religious organization Little Sisters of Divine Providence, started the process by remodeling daily living practice, of which the women were the center of the family, as wives and mothers. The model of femininity as adopted by the religious order, hegemonic in much of the westernization, was the one in which the woman would only find fulfillment and true happiness in the domestic environment. To realize this task, we designed a series of popular courses directed to the domestic space, enhancing the image of the woman as wife, housewife and family mother.
Keywords: gender; family; biopolitics